Use of carbonised wood particles as filler replacement in hot mix asphalt - Rengarasu, T. M.; Jegatheesan, N.; Bandara, Wasala M.K.R.T.W. (National Science Foundation: Colombo, 2026)
This study investigated the feasibility of using carbonised wood particles (CWP) as a sustainable filler replacement in hot mix asphalt (HMA), addressing both environmental concerns and construction material performance. Despite considerable research, the moisture susceptibility of HMA modified with CWP, possessing a wider particle size distribution, remains unestablished. Twenty five HMA mixes with varying CWP content (0 to 40 g, equivalent to 0 24% filler replacement by mass) and asphalt content (4 – 6%) were evaluated against ASTM standards for their Marshall stability and indirect tensile strength, moisture susceptibility, and water absorption. The results indicate a clear trade-off: incorporating CWP improved physical properties like void structure but significantly reduced the mechanical strength and moisture resistance. Marshall stability and indirect tensile strength decreased by up to 79% and 75%, respectively, with higher CWP contents. The study conclusively identified 12% CWP replacement (20 g) as the optimal dosage. This proportion maintains acceptable performance for medium-traffic highways while delivering significant sustainability benefits by reducing reliance on quarried mineral filler and repurposing industrial waste. This optimal balance offers a viable pathway for more eco-friendly pavement construction without compromising critical performance criteria for specific applications.
Keywords: Carbonised wood particles; Hot mix asphalt; Mineral filler; Indirect tensile strength; Marshall properties